2017
DOI: 10.1021/acs.orglett.7b01833
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free “On-Water” Regio- and Stereospecific Ring-Opening of Spiroaziridine Oxindole: Enantiopure Synthesis of Unsymmetrical 3,3′-Bisindoles

Abstract: A catalyst-free water-mediated regio- and stereospecific ring-opening reaction of nonracemic spiroaziridine oxindoles and indoles has been developed with retention of configuration. This method provides direct access to enantiopure 3,3'-mixed bisindoles with excellent yield and enantioselectivity (up to 98% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…According to Jung‐Marcus theory, approximately 25 % of water molecules having free OH groups at the interface are available for potential H‐bonding with the substrate on the surface. Recently, we discovered catalyst‐free on‐water regio‐ and stereoselective ring opening of spiroaziridine oxindoles with indoles . This led us to presume that water can also activate spiro‐epoxyoxindole similar to that of spiro‐aziridine.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…According to Jung‐Marcus theory, approximately 25 % of water molecules having free OH groups at the interface are available for potential H‐bonding with the substrate on the surface. Recently, we discovered catalyst‐free on‐water regio‐ and stereoselective ring opening of spiroaziridine oxindoles with indoles . This led us to presume that water can also activate spiro‐epoxyoxindole similar to that of spiro‐aziridine.…”
Section: Resultssupporting
confidence: 80%
“…Eventually, we have observed that catalytic amount of Brønsted acid in organic solvent can also activate the spiro‐epoxide and lead to regioselective ring opening at the tertiary centre by the carbon nucleophiles likely indoles and arenes. Moreover, we have recently reported catalyst free on‐water ring opening reaction of spiro‐aziridineoxindole and indole . This result again encourages us to find an environment friendly greener approach for this ring‐opening reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Hajra and co‐workers utilized similar reaction conditions for the enatioselective synthesis of bis‐indoles by ring opening of spiroaziridines indoles and oxyindoles. According to their report hydrogen‐bonding between aziridines and water molecules was primarily responsible for the activation of aziridine as well as for the high enatioselectivity …”
Section: Ring Opening Of Aziridine In Watermentioning
confidence: 99%
“…An excellent work by Hajra and co‐workers describe the first catalyst/reagent‐free stereocontrolled carbon−carbon bond forming reaction utilising on water protocol . Ring‐opening reactions of chiral spiroaziridineoxindoles with indoles at 80 °C, resulted in enantiopure 3,3′‐mixed bisindoles (Scheme ).…”
Section: Direct Functionalisation Reactionsmentioning
confidence: 99%